Wherefore Moot Court? - Richard E. Finneran (Washington University Journal of Law & Policy, 2017)
This Essay, by Richard E. Finneran, adjunct professor and moot court coach at Washington University School of Law, extols the benefits of participating in moot court programs and offers tips how to instruct students to become better appellate advocates. Finneran underscores the value of studying oral advocacy, particularly as the decline in popularity studying and teaching the art of oral argument is reflected in the lack of quality exhibited by some advocates. Finneran does not attribute this lack of quality on the innate skills of an advocate, but rather places the onus on educators to teach moot court students the importance of crafting good arguments and answers.
Keywords: moot court; appellate advocates; law school; law students; Supreme Court oral arguments; federal court of appeals; appellate advocacy; oral advocacy; oral argument